PEMBERDAYAAN KARANG TARUNA DALAM PENGOLAHAN LIMBAH TERNAK SAPI, ARANG SEKAM, DEDAK PADI SEBAGAI PUPUK BOKASHI - Mutmainna; Ali Tahir, Muhammad; Muhammad Irfan Taufan Asfar, Andi; Muhamad Iqbal Akbar Asfar, Andi; Nurannisa, Andi; Amalia, Nur; Widia Diningsih, Andi (JCOMMITS: Journal of Community Empowerment, Inovation, and sustainability, 2023)
The problem of cow dung waste in Tappale Village, especially for Karang Taruna Sipabokori partners in Tappale Village, is still a crucial problem. So far, cow dung waste has only been thrown away and piled up, sometimes people even throw it in waterways, thereby polluting the environment. Therefore, with the Community Service Program (PKM-PM) activities, we will provide a solution to Karang Taruna Sipabokori partners in Tappale Village in processing cow dung waste into bokashi fertilizer as an alternative companion fertilizer. The implementation method for PKM-PM activities is carried out in three stages, namely the counseling or socialization stage, the training stage and the mentoring stage. The results of implementing PKM activities for partners showed a significant increase in knowledge and skills regarding the benefits of cow dung waste and partners were able to process cow dung waste into bokashi fertilizer with additional supporting materials, namely husk charcoal and rice bran with an increase of 90%, packaging and labeling reached 90% percentage and marketing reach 100% percentage.